ESG-score effect in risk assessment of direct and portfolio investment: evidence from CEE markets - Andriy Kaminskyi; Maryna Nehrey; Anastasiia Fedchun (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2022)
The inclusion of ESG factors (Environmental, Social, Governance) in the assessment of investment attractiveness is a dynamic trend in the current period. The integrated indicator of these factors is the ESG score. In the paper, the authors examined the interdependencies between the three indicators: ESG scores, expected returns, and risks. The survey was conducted for 21 companies from Central and Eastern Europe. The inverse relationship between ESG score and risk is shown, as well as the practical absence of a relationship with expected returns. ESG score effect in risk assessment of direct and portfolio investment was identified and analyzed.